PEDAGOGY OF CARE AND RELATIONAL ETHICS IN EDUCATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the theoretical foundations and educational implications of the Pedagogy of Care and Relational Ethics in contemporary education. Drawing primarily on the ethics of care tradition, particularly the work of Nel Noddings, the paper conceptualizes teaching as a fundamentally relational, ethical, and moral practice rather than a purely technical activity. The discussion examines how caring relationships between teachers and students contribute to inclusive learning environments, learner motivation, and academic success. In addition, the article analyzes relational ethics as a framework for ethical decision-making in education, emphasizing contextual judgment, responsibility, and dialogical interaction. Critical perspectives are also considered, including issues of emotional labor, power asymmetry, and institutional constraints. The article concludes that integrating carebased pedagogy and relational ethics can enhance educational equity, teacher professionalism, and the humanistic quality of education, provided that such approaches are supported at both pedagogical and policy levels.